IDEOLOGICAL PARAMETERS FOR DERADICALIZATION PROGRAMS TO MEASURE CHANGES IN TERRORIST IDEOLOGY IN INDONESIA - Zulfahri, Yudi; Auliya, Aldi Nur Fadil (Journal of Terrorism Studies, 2023)
The paper analyzes the inefficiency of the Deradicalization strategy implemented by The National Counter Terrorism Agency (BNPT), causing the issue of recidivist terrorism in Indonesia. Although the occurrence of recidivism is common in various crimes, it poses unique challenges in terrorism cases, given that the government has allocated a specific budget and established a special agency, BNPT, to tackle terrorism-related issues. The high recidivism rate in terrorism cases has prompted public concern and criticism regarding the effectiveness of Deradicalization programs. Despite the ongoing debate, this paper argues that the success or failure of Deradicalization programs cannot be measured simply by the high recidivism rates. This is because the rehabilitation of terrorists is a dynamic and progressive process that requires continuous evaluation. The authors suggest that the main problem with the program lies in the absence of clear parameters to assess the process of changing terrorist ideology, leading to biased assessments. Therefore, this paper attempts to reconceptualize appropriate Deradicalization strategies to measure and ensure the ideological changes of terrorists. The study begins with redefining the meaning of terrorism, identifying terrorist groups in Indonesia, mapping the ideology of terrorist groups, establishing ideological parameters of terrorism, and devising appropriate Deradicalization strategies to rehabilitate terrorists in Indonesia.